Pertumbuhan dan Hasil Beberapa Varietas Tanaman Bawang Merah (Alium ascalonicum L.) Akibat Pemotongan Umbi - Laila Nazirah; Anjas Maulana (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2020)
Onions (Allium ascalonicum L) are one of the horticultural crops that are widely used as a seasoning mixture.One of the important factors in onion cultivation is the selection of varieties.In addition to the selection of varieties, cutting the tip of the tuber 1/4 or 1/3 is possible to stimulate buds, accelerate growth and establishment of seedlings.This research aimed to study and evaluate the growth and yield response of several onion varieties due to tuber cutting treatment..This research was carried out in the Tambon Tunong community garden, Dewantara District, North Aceh Regency and the Malikussaleh University Agricultural Laboratory, starting from February 2020 to April 2020.This study used a factorial randomized block design consisting of 9 treatment combinations with 3 replications in order to gain 27 experimental units.The first factor is the onion varieties, while the second factor is cutting the tubers, each consisting of 3 levels of treatment.The results showed that the different varieties had a very significant effect on plant height, number of leaves, number of tillers, wet and dry weight of tubers.Tuber cutting treatment has a significant effect on tuber yield.Treatment interactions were obtained on the number of tillers due to tuber cutting treatments and the use of different varieties.The best treatment was obtained in Bauji varieties by cutting 1/3 of the onion bulb.